C-Arm Computed Tomography-Assisted Adrenal Venous Sampling Improved Right Adrenal Vein Cannulation and Sampling Quality in Primary Aldosteronism - Chung Hyun Park; Namki Hong; Kichang Han; Sang-Wook Kang; Cho Rok Lee; Sungha Park; Yumie Rhee (Endocrinology and Metabolism, 2018)
BackgroundAdrenal venous sampling (AVS) is a gold standard for subtype classification of primary aldosteronism (PA). However, this procedure has a high failure rate because of the anatomical difficulties in accessing the right adrenal vein. We investigated whether C-arm computed tomography-assisted AVS (C-AVS) could improve the success rate of adrenal sampling.MethodsA total of 156 patients, diagnosed with PA who underwent AVS from May 2004 through April 2017, were included. Based on the medical records, we retrospectively compared the overall, left, and right catheterization success rates of adrenal veins during the periods without C-AVS (2004 to 2010, n=32) and with C-AVS (2011 to 2016, n=124). The primary outcome was adequate bilateral sampling defined as a selectivity index (SI) >5.ResultsWith C-AVS, the rates of adequate bilateral AVS increased from 40.6% to 88.7% (P<0.001), with substantial decreases in failure rates (43.7% to 0.8%, P<0.001). There were significant increases in adequate sampling rates from right (43.7% to 91.9%, P<0.001) and left adrenal veins (53.1% to 95.9%, P<0.001) as well as decreases in catheterization failure from right adrenal vein (9.3% to 0.0%, P<0.001). Net improvement of SI on right side remained significant after adjustment for left side (adjusted SI, 1.1 to 9.0; P=0.038). C-AVS was an independent predictor of adequate bilateral sampling in the multivariate model (odds ratio, 9.01; P<0.001).ConclusionC-AVS improved the overall success rate of AVS, possibly as a result of better catheterization of right adrenal vein.